2021
DOI: 10.1016/j.cell.2021.02.042
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 501Y.V2 variants lack higher infectivity but do have immune escape

Abstract: The 501Y.V2 variants of SARS-CoV-2 containing multiple mutations in Spike are now dominant in South Africa and are rapidly spreading to other countries. Here, experiments with 18 pseudotyped viruses showed that the 501Y.V2 variants do not confer increased infectivity in multiple cell types except for murine ACE2-overexpressing cells, where a substantial increase in infectivity was observed. Notably, the susceptibility of the 501Y.V2 variants to 12 of 17 neutralizing monoclonal antibodies was substantially dimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
346
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 356 publications
(373 citation statements)
references
References 47 publications
19
346
0
Order By: Relevance
“…Molecular dynamic simulation reveals E484K mutation enhances spike RBD-ACE2 affinity and the combination of E484K, K417N and N501Y mutations (501Y.V2 variant) induces a higher number of conformational changes than N501Y mutant alone, potentially resulting in an escape mutant (Nelson et al 2021) . Since this site is not involved in interaction with hACE-2 when the original glutamate is in place, its occurrence has been linked to reinfection, convalescent plasma activity abolishment and decreased post-vaccination neutralizing activity (Nelson et al 2021;Li et al 2021) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamic simulation reveals E484K mutation enhances spike RBD-ACE2 affinity and the combination of E484K, K417N and N501Y mutations (501Y.V2 variant) induces a higher number of conformational changes than N501Y mutant alone, potentially resulting in an escape mutant (Nelson et al 2021) . Since this site is not involved in interaction with hACE-2 when the original glutamate is in place, its occurrence has been linked to reinfection, convalescent plasma activity abolishment and decreased post-vaccination neutralizing activity (Nelson et al 2021;Li et al 2021) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the three main lineages (B.1.1.54, B.1.1.56 and C.1), which represented the majority of cases in the first wave, were responsible for~42% total of the infections by the end of 2020, since B.1.351 had emerged in an explosive fashion in mid-October (Tegally et al 2021) . This later lineage is of major concern and South Africa is, up to February 2021, the leader country in COVID-19 related deaths in Africa (Li et al 2021;Johns Hopkins Coronavirus Resource Center, 2021) . In Brazil, the prevalence of lineages B.1.1.28 and its derivatives P.1 and P.2 have been representing progressively more cases of the sequenced genomes by the time of writing.…”
Section: Discussionmentioning
confidence: 99%
“…E484K was responsible for near complete resistance against multiple NTD and RBD mAbs and up to >10 and >30 times lower nAb titers in vaccinees and convalescent individuals, respectively. N501Y or K417N are additional mutations, all in RBD, conferring reduced nAb activity in SARS-CoV-2 vaccine and convalescent sera [292,293,296,297,[321][322][323][324][325][326][327][328]. These results could be recapitulated in experiments with SARS-CoV-2 isolates [329][330][331], whereas another study with recombinant SARS-CoV-2 carrying the specific point mutations reported smaller effects on nAb titers against infectious SARS-CoV-2 [332].…”
Section: Sars-cov-2 Mutates On a Low But Constant Level Yielding Mutant Variants Over Timementioning
confidence: 87%
“…However, as viruses possess various mutational strategies, viral mutations may arise and reduce the affinity of antibody drugs. In the case of COVID-19, for instance, emerging variants have begun to exhibit the capability to escape from neutralizing antibodies [111,112]. As receptor-mediated binding with surface molecules on the plasma membrane of cells is an indispensable process for viruses to invade host cells [113], this interaction has been exploited to design biomimetic nanoparticle possessing cell-like surfaces for virus targeting.…”
Section: Biomimetic Nanoparticles For Active Targeting Of Viruses Andmentioning
confidence: 99%